Development of mixed matrix membranes for controlled release of ibuprofen. Issue 1 (17th July 2012) - Algieri, C.; Drioli, E.; Donato, L.
Abstract In this work was studied the effect of different zeolite topologies on the release of ibuprofen from mixed matrix membranes (MMMs). The main parameters investigated were: zeolite concentration, its hydrophilic/hydrophobic character, and drug loading. About the different investigated systems, the PDMS NaX (I) membrane seems to be the most promising for its application as transdermal device. The release data were fitted with different mathematical models (zero order, first order, Higuchi, Bhaskar, and Korsemeyer‐Peppas) to give a possible explanation of the release mechanism of the drug from MMMs. The release data of the drug from pure PDMS membranes (PDMS IBU) were fitted by the Higuchi model (R2 pari a 0.97). In the case of MMMs, the correlation coefficients are very far from the unit value except for the PDMS NaX (I) system that obeys to the Korsmeyer–Peppas (0.98) and Bashkar (0.99) models. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013